Clinical Pearls for Initiating and Utilizing Liraglutide in Patients With Type 2 Diabetes. (April 2013) - Gross, Benjamin
This review presents clinical pearls for initiating liraglutide (Victoza®, Novo Nordisk Inc) therapy for the management of type 2 diabetes and selecting patients who will benefit from liraglutide therapy. Liraglutide, a once-daily glucagon-like peptide 1 receptor agonist, is Food and Drug Administration approved as an adjunct to diet and exercise to improve glycemic control in adults with type 2 diabetes. Liraglutide is effective for reducing hemoglobin A1c levels by 0.8% to 1.5% in patients with type 2 diabetes as monotherapy or in combination with other diabetic medications (such as metformin, sulfonylureas, rosiglitazone, or basal insulin) when compared with placebo and these other diabetic medications, including exenatide. Overweight or obese patients with type 2 diabetes or those with insulin resistance are good candidates for liraglutide therapy because liraglutide use is associated with weight loss (about 2%-4% of initial body weight) and improved β-cell function. The incidence of hypoglycemia with liraglutide is low; therefore, liraglutide would be a safe therapy choice for patients at risk or with a history of symptomatic or severe hypoglycemia. Nausea seems to be the most problematic adverse effect associated with liraglutide therapy, but it is usually transient and is minimized with dose titration.